2014
DOI: 10.1055/s-0034-1365524
|View full text |Cite
|
Sign up to set email alerts
|

How commonly is upper gastrointestinal cancer missed at endoscopy? A meta-analysis

Abstract: Background and study aims: Upper gastrointestinal (UGI) cancer in the Western world usually presents at an advanced stage, when opportunities for curative therapy are limited. The failure to detect subtle, early-stage UGI cancer at endoscopy may contribute to a poor prognosis. We undertook a meta-analysis of studies of endoscopic miss rates for UGI cancer to quantify how often opportunities to diagnose cancer at an earlier stage are missed. Patients and methods: A MEDLINE search was conducted to identify relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
196
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(204 citation statements)
references
References 14 publications
2
196
1
5
Order By: Relevance
“…[3][4][5][6][7][8][9][10] A meta-analysis from 2014 confirms these findings. 11 This result is comparable to post-colonoscopy colorectal cancer rates of 2.5-7.7% in Western populations. 12 Notably, upper gastrointestinal cancer miss rates in some studies from the Far East are higher than those reported for the West, [13][14][15][16] but these series include early gastric neoplasia, whereas the Western publications report predominantly advanced cancers (Table 1).…”
Section: Introductionsupporting
confidence: 58%
“…[3][4][5][6][7][8][9][10] A meta-analysis from 2014 confirms these findings. 11 This result is comparable to post-colonoscopy colorectal cancer rates of 2.5-7.7% in Western populations. 12 Notably, upper gastrointestinal cancer miss rates in some studies from the Far East are higher than those reported for the West, [13][14][15][16] but these series include early gastric neoplasia, whereas the Western publications report predominantly advanced cancers (Table 1).…”
Section: Introductionsupporting
confidence: 58%
“…Although similar studies are yet to be conducted, it seems likely that the same will apply to OGD 23–26. Poor tolerance of OGD may be associated with a reduced lesion detection rate,27 and some studies suggest that sedation, particularly for anxious patients, may improve tolerance 28 29. Patients should have had their H. pylori status checked prior to referral5 and appropriate notification on the referral form should render rapid urease testing unnecessary for most.…”
Section: Discussionmentioning
confidence: 99%
“…(23) Most gastric cancers found within 1 year after eradication may have been missed on previous endoscopic screenings. (24) It is well known that H. pylori infection causes endoscopic gastritis, which presents as erythema, erosion, hemorrhage, and large gastric folds. (16) H. pylori eradication improves gastritis as determined endoscopically and histologically.…”
Section: Discussionmentioning
confidence: 99%